Strategi Konsumsi Rumah Tangga di Tengah Tekanan Inflasi Dalam Perspektif Ekonomi Syari’ah - Mahtufatul Mukarromah; Haqiqotus Sa’adah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the consumption strategies of Muslim households in facing inflation from the perspective of Islamic economics. Inflation increases the prices of basic goods and reduces purchasing power, thereby forcing households to adjust their consumption patterns in order to maintain family economic stability. This research uses a qualitative field approach conducted in Patemon Village, Tlogosari District, Bondowoso Regency. Data were collected through interviews, observation, and documentation, then analyzed descriptively and analytically by integrating conventional consumption theory and Islamic economic principles. The findings show that Muslim households apply several adaptive strategies, including reducing secondary consumption, adjusting spending priorities, substituting consumption goods, diversifying income sources, and utilizing social and religious networks. From the perspective of Islamic economics, household consumption behavior is not only oriented toward fulfilling material needs, but also considers halal, tayyib, maslahah, falah, qana’ah, and the prohibition of israf. These findings indicate that Islamic economics provides a strong normative foundation for shaping simpler, more rational, and more sustainable consumption behavior amid inflationary pressure.